5y+9=x-23

Simple and best practice solution for 5y+9=x-23 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5y+9=x-23 equation:


Simplifying
5y + 9 = x + -23

Reorder the terms:
9 + 5y = x + -23

Reorder the terms:
9 + 5y = -23 + x

Solving
9 + 5y = -23 + x

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-9' to each side of the equation.
9 + -9 + 5y = -23 + -9 + x

Combine like terms: 9 + -9 = 0
0 + 5y = -23 + -9 + x
5y = -23 + -9 + x

Combine like terms: -23 + -9 = -32
5y = -32 + x

Divide each side by '5'.
y = -6.4 + 0.2x

Simplifying
y = -6.4 + 0.2x

See similar equations:

| .3X=Y-X | | 21x-19sinx=5 | | 8-7x=7+8x | | x+7y=52 | | 1-3(2.x-1)=6 | | 3x-5(x-4)=-6+4x+14 | | 9=y/335 | | M^2+5m-3= | | 3+.03(115)= | | 4x=8y+1 | | 2(X+4)=3x-11 | | m=5-2sinx | | (13×3)-3)/3 | | 9/24/=12/n | | 0.5x-0.5=x+1.5 | | -75+7.5t=150 | | 2y(dx)+3x(dy)=0 | | 240=3v+f | | 7x^4=1 | | 5(y+2)=(2y+2) | | 3.15(x)+y=45 | | 3/4k-10=3 | | (8x^3+8x^2-40x+24)(4x^3+20x^2+12x-36)= | | y=1/4(8)-7 | | 1/2÷9 | | 3(5)+5(3)= | | x=8^(3/7) | | A-21=19 | | 3/y=y | | -1-2y=1 | | 2x-5(x-3)=-6+5x-43 | | 0.13x+x=25 |

Equations solver categories